Stabilność lokat bankowych gmin w Polsce - Paweł Galiński (Problemy Zarządzania, 2015)
The aim of the article is to characterize the stability of bank deposits of each type of the communes in Poland as well as the main determinants of their value. The research time range covers the period 2008–2014. In this period, some legal and financial determinants of deposit activity of these units appeared. The activity of the communes in this field simultaneously influences the stability of sources of funding of banks, which include deposits of these entities. This especially concerns cooperative banks, which are natural clients for rural communes and urban-rural communes, as units from the public finance sector in Poland.